Evaluasi Kinerja Perusahaan Berdasarkan Perspektif Organisasi, Proses, dan Staf Berbasis AHP dan OMAX - Sari, Ratih Ardia; Yuniarti, Rahmi; Safitri, Farida Risqi Nur (Jurnal Teknik Industri, 2018)
Performance measurement is done to measure the achievement of the company. Performance is made to know the company is reaching its target. In this research, the company's performance in the field of electrical contractor is measured. Key Performance Indicator (KPI) used from the perspective of the organization, process, and staff. Weighting KPI using Analytical Hierarchy Process. Objective Matrix and Traffic Light System are used for the scoring system. The results showed that from 23 KPI got 9 KPI is in the red zone, 10 in the yellow zone and the rest in the green zone. From these results then the company needs improvement to improve performance.